FEMINISM and FEMINIST GROUNDED THEORY: A Comprehensive Research Analysis - Mohajan, Haradhan Kumar (Journal of Economic Development, Environment and People, 2022)
The purpose of this paper is to flourish the grounded theory (GT) methodology in qualitative research from the feminist viewpoint. Since the mid-1990s feminist researches on grounded theory have been started and researchers have been using this approach for the research on the basis of practical experiences. The nursing researchers, for the first time, draw on feminist principles in grounded theory for the better serving of the interests of women in healthcare. Feminist grounded theory (FGT) is the evolved form of the original grounded theory of Glaser and Strauss. Feminist research is a related area of social research and always thinks welfare of the women, especially those who are under estimated in the male dominated society. In every country some professions, such as nursing, home economics, nutrition, etc. are women dominated. Feminist grounded theory methodology research is well-fitted in these areas. In the 21st century, feminist grounded theory is appropriate, effective, and highly resourceful. In the past, women’s voices and views are frequently ignored in many cases, such as in academics and policy making. At present, feminist research is a growing field in research arena that creates concerns about the rights of women, and provides knowledge to bring them in light. This study exercises feminism and the structure of feminist nature of the grounded theory to change subordination of women and to reduce social inequality in all stages. The aim of this paper is to discuss and analyze feminist epistemologies and to highlight necessity of feminist grounded theory in the society.